CRYSTALLOGRAPHIC CHARACTERIZATION OF TETRADENTATE SCHIFF BASE COMPLEXES OF COBALT(II), NICKEL(II), AND COPPER(II) (International Journal of Food and Nutritional Sciences, 2023)
This paper presents the structural studies of chelates formed by cobalt (II), nickel (II), and copper (II) ions with a tetradentate Schiff base ligand. The synthesis of the Schiff base ligand and its subsequent coordination with the metal ions were carried out using standard procedures. Structural characterization of the resulting metal-ligand complexes was performed using X-ray crystallography, UV-Vis spectroscopy, and FTIR spectroscopy. The obtained structural data revealed the coordination geometries, bond lengths, and bond angles of the complexes. Comparative analysis of the complexes formed with cobalt (II), nickel (II), and copper (II) ions elucidated the influence of the metal center on the resulting structures. The spectral data provided additional insights into the coordination modes and bonding interactions within the complexes. Overall, this study contributes to the understanding of coordination chemistry and provides valuable insights into the structural properties of metal-ligand complexes with tetradentate Schiff base ligands.